Pengembangan Panduan Konseling Psikoreligius Untuk Remaja Korban Kekerasan - Miftahus Surur; Yulia Sholichatun (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
The purpose of this study was to develop a guide to psycho-religious counseling and examine whether psychiatric counseling guidelines can help overcome the effects of violent trauma on adolescents. The method used is the research and development (R & D) model. The procedure of development research includes: 1) the preparation stage, 2) the implementation stage, namely drafting the product, and 3) product testing or product validation and preparation of the final product. This product is tested by a team of experts consisting of a religious expert and a psychologist and validated by experts. In the implementation phase an assessment of the symptoms of post-traumatic stress experienced by teenage respondents who were victims of violence was conducted before counseling and after counseling. Research data were analyzed quantitatively descriptive and qualitative. The results show that counseling guidelines have been developed validally both in terms of usability, accuracy, suitability and ease of guidance in the implementation of counseling for adolescents who are victims of violence. The results of the qualitative analysis of three teenage respondents who were victims of violence at the time of implementation of the guidelines also showed a decrease in symptoms of post-traumatic stress and an increase in religious behavior after attending psycho-religious counseling.